Social environment determinants of life expectancy in developing countries: a panel data analysis - Hassan, Fatin Aminah; Minato, Nobuaki; Ishida, Shuichi; Mohamed Nor, Norashidah (Canadian Center of Science and Education, 2017)
Despite remarkable improvements in health over the past 50 years, there still remain a great number of health challenges around the world. This study examined the relationship between life expectancy rate (as a proxy for health status) with health expenditure, gross domestic product, education index, improved water coverage, and improved sanitation facilities in 108 selected developing countries using annual panel data within the period of 2006–2010. The empirical results from using the panel data approach showed a positive relationship between life expectancy rate and all of those explanatory variables. The relationship between life expectancy with education index and gross domestic product were significant at 1% and 5% significance levels, respectively. Furthermore, the causality finding showed that there is no short-run causality between life expectancy and its determinants. There is a unidirectional causality running from the independent variables of health expenditure, education index, improved water, and improved sanitation to life expectancy at birth. On the other hand, bidirectional causality exists between life expectancy and income in the long-run by employing VECM test. These independent variables can be considered as important determinants for investment in health status in the long-run. This study could be used as a guideline and may be significant for future researchers and policy makers who aim to improve the life expectancy in developing countries.